Pelubiprofen is a new member of the class of non-steroidal anti-inflammatory drugs for the treatment of back pain and pain in rheumatic musculoskeletal disorders - A. M. Lila; V. A. Parfenov; A. E. Karateev; T. V. Adasheva; L. I. Alekseeva; V. V. Afanasyev; E. R. Barantsevich; O. V. Vorobyeva; O. S. Davydov; E. V. Ekusheva; A. I. Zagrebneva; D. A. Iskra; et al. (Современная ревматология)
On December 18, 2024, a meeting of the Expert Council was held to discuss approaches to the treatment of non-specific back pain and pain in rheumatic musculoskeletal disorders. It was noted that non-steroidal anti-inflammatory drugs (NSAIDs) remain the mainstay of therapy for inflammation-related pain and that optimal therapy should provide a balance between high efficacy and good tolerability in each patient. A new NSAID, pelubiprofen (Pelubio®), has been registered in the Russian Federation. According to research data, its efficacy is comparable to that of non-selective and selective NSAIDs and at the same time the drug has a high safety profile. The resolution of the Expert Council states that this medicine can be prescribed within the framework of Russian clinical practice, considering the registered indications for pelubiprofen and the clinical guidelines adopted in Russia for the treatment of acute and chronic non-specific back pain, radiculopathy, osteoarthritis (including gonarthrosis and coxarthrosis) and rheumatoid arthritis.